Knowledge management and SMEs’ digital transformation : A systematic literature review and future research agenda - Hafeez, Shahid; Shahzad, Khuram; Helo, Petri; Mubarak, Muhammad Faraz (Elsevier, 2025)
This study aims to identify and explain different collaborative approaches, delineate external actors' roles, and examine the interplay between knowledge exploration and exploitation processes for digital transformation. We conducted a search of academic papers using research terms such as “Digital*, Digital transfor*, industry 4.0 (I4.0), industry 5.0, knowledge exploration, knowledge acquisition, ecosystem collaboration*, knowledge networks, and open innovation” in both the Scopus and Web of Science databases. Altogether, 108 papers met the criteria (e.g., ABS 2 & 2+ ranking of journals, only journal papers, and focusing on small- and medium-size enterprises (SMEs) digital transformation) for conducting a systematic literature review in this research. The results indicate that external actors play specific roles in supporting SMEs' digital transformation. We found that customers and suppliers push and encourage SMEs in their digital transformation, while coopetition can elicit greater technological benefits for SMEs with close technological and economic proximity. Intermediaries provide knowledge-brokering services, facilitate innovation processes, and enable technology transfer and capacity-building for SMEs’ digital transformation. Government initiatives, such as favorable policymaking and financial support, are important in promoting and facilitating a collaborative environment for technology development among SMEs. This study’s results present two distinct collaborative mechanisms that SMEs can utilize for digital transformation: (I) core value chain and network actors’ collaborations, which provide linear processes for knowledge exploration and exploitation, and (II) ecosystem and innovation platform-based collaborations, in which SMEs adopt the ambidextrous approach as a nonlinear process for knowledge exploration and exploitation for digital transformation. Certain organizational-level factors (organizational capabilities, micro-foundations, operational capabilities, organization strategies, and culture) are important for SMEs’ knowledge exploitation in digital transformation. The study also presents an integrated framework and offers directions for future research and important insights for practitioners.
Keywords: SMEs; Digital transformation; Knowledge exploration; Knowledge exploitation; Ecosystem; Platform; Systematic literature review; Capabilities; small and medium-sized enterprises; knowledge management; fi=Markkinointi|en=Marketing|; fi=Tuotantotalous|en=Industrial Management|